Transizione demografica e formazione del risparmio delle famiglie italiane - Massimo Baldini; Carlo Mazzaferro (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
– This paper studies the relationship between population ageing and saving formation by Italian households. We use five cross-sectional budget surveys to separately construct the age and cohort profiles of the saving rate. After detrending the data, we isolate the age and cohort effects on saving. Cohort effects show that, in the current Italian population, saving behaviour is markedly different across generations. The estimates obtained on survey data are then used to derive a forecast of the medium and long run tendency of the household saving rate (2000-2050). In the absence of any changes in the saving behaviour of young cohorts, the saving rate falls by 15% at the end of the period. The recent reforms of the pension system could induce the young to increase their saving, but the available empirical evidence leads to a scenario where the effects of the pension reform on the incentive to save and accumulate are low, and may be neutralised by the mechanism of intergenerational transfers. Even in a scenario where the young actually react to the pension reform, the reduction in total household wealth at the end of the life-cycle leads to a decrease in aggregate household saving.
Keywords: 330